An experimental and theoretical study of magnetocaloric effect in Nd0.5Dy0.5FeO3. (12th June 2019) - Singh, Ankita; Rajput, Sarita; Padmanabhan, B; Kaushik, Kedarsh; Anas, M; Maitra, T; Malik, V K
Abstract: A significant magnetocaloric effect (MCE) has been revealed in our investigation on polycrystalline Nd0.5 Dy0.5 FeO3 below 30 K. Observed magnetization of the system at low temperature is 32% higher than the expected average magnetization of NdFeO3 and DyFeO3 . Such an enhancement in the magnetization led to a large change in magnetic entropy (10.4 Jkg −1 K −1 ) at 4 K. The observed entropy change is remarkable considering the higher natural abundance of Nd compared to that of Dy and negligible MCE seen in case of NdFeO3 . Theoretical calculations performed using mean-field approximation and Monte Carlo simulations on an Ising type spin model indicate that the high magnetocaloric effect is caused primarily by the ordering of rare-earth ions in C-type antiferromagnetic state in presence of molecular exchange field created by Fe ions.